Kontribusi Hermeneutika Hans-Georg Gadamer Bagi Ilmu Pengetahuan - Ambrosius M. Loho (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
This paper will outline the position of Hans Georg Gadamer's thoughts about Hermeneutics, among the sciences. Hermeneutics Gadamer becomes important to acquire knowledge, because beside the hermeneutics, there are also other methods of acquiring knowledge. In essence, science only provides an explanation that is limited in nature, and limits to the goals or in certain fields. Likewise, when there is an absolute reversal of one method, at the same time, philosophy as a critical science is turned off, because the person not able to answer the radical methods. In other words, it is believed that science only studies in very limited terms and not in-depth. Because of that fact, philosophy is here to give a radical foundation on how to solve life's problems, including science. Keywords: hermeneutics, sciences, science.